Google econometrics and unemployment forecasting - Nikolaos Askitas; Klaus F. Zimmermann (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The current economic crisis requires fast information to predict economic behavior early, which is difficult at times of structural changes. This paper suggests an innovative new method of using data on internet activity for that purpose. It demonstrates strong correlations between keyword searches and unemployment rates using monthly German data and exhibits a strong potential for the method used.
Keywords: C22; C82; E17; E24; E37; 330; Google; internet; keyword search; search engine; unemployment; predictions; time-series analysis